The lipidomics reporting checklist a framework for transparency of lipidomic experiments and repurposing resource data - Kopczynski, Dominik; Ejsing, Christer S.; McDonald, Jeffrey G.; Bamba, Takeshi; Baker, Erin S.; Bertrand-Michel, Justine; Brügger, Britta; Coman, Cristina; Ellis, Shane R.; Garrett, Timothy J.; Griffiths, William J.; Guan, Xue Li; et al. (Journal of lipid research, 2024)
The rapid increase in lipidomic studies has led to a collaborative effort within the community to establish standards and criteria for producing, documenting, and disseminating data. Creating a dynamic easy-to-use checklist that condenses key information about lipidomic experiments into common terminology will enhance the field's consistency, comparability, and repeatability. Here, we describe the structure and rationale of the established Lipidomics Minimal Reporting Checklist to increase transparency in lipidomics research.